Mechanical and Microstructural Proxies of LC³ Mortars up to 50% Clinker Replacement Using a Southern Libyan Calcined Kaolinite Clay. - M. Elshibani, Zainab; H. Abdalkader, Ashraf (Scientific Journal of University of Benghazi, 2025)
ABSTRACT This experimental study investigates the properties of LC³ (limestone-calcined clay) cement mortars with high clinker replacement, utilizing locally sourced kaolinite-rich clays from southern Libya. Mortar mixtures were prepared with clinker contents of 40, 50, and 60%. The mechanical performance of the LC³ blends was assessed through compressive and flexural strength tests, ultrasonic pulse velocity (UPV), porosity measurements, and workability evaluations. The results show that replacing up to 50% of cement with a limestone–calcined clay blend in mortar mixes achieves compressive and flexural strengths comparable to, or slightly exceeding, those of ordinary cement. At 28 days, mortars with 50% substitution reached the same compressive strength as CEM I (37 MPa) while exhibiting a 19.6% increase in flexural strength. Furthermore, higher replacement levels (up to 50%) improved pore structure refinement, leading to a denser microstructure. Mortars with 50% substitution demonstrated about a 9.65% reduction in porosity compared to CEM I.